Description of a new genus of ponyfishes (Teleostei: Leiognathidae), with a review of the current generic-level composition of the family - Sparks, John S.; Chakrabarty, Prosanta (Zootaxa, 2015)
In order to recognize a monophyletic taxonomy for Leiognathidae based on unique features of the bacterially mediated light-organ system, we describe a new sexually-dimorphic genus of elongate, shallow-bodied ponyfishes within the tribe Equulitini, which itself is recovered within the subfamily Gazzinae. Photolateralis, new genus, is unique among ponyfishes in possessing a translucent mid-lateral flank stripe, which depending on the species, may be either a composite “stripe” comprised of numerous independent translucent windows (P. stercorarius and P. moretoniensis), or a continuous translucent lateral stripe (P. antongil). This translucent lateral stripe is either lacking entirely in females, or is considerably less well developed. In contrast, males in its sister taxon, Equulites, are characterized by the presence of an expansive, triangular, translucent lateral flank patch that also exhibits species-specific morphology. Internally, in Photolateralis the light organ system is characterized by a moderately enlarged, donut-shaped, and conspicuously spotted light organ in males that extends only slightly posteriorly into the gas bladder. In contrast, in members of Equulites the dorsolateral lobes of the light organ in males are greatly enlarged, heavily pigmented, and extend posteriorly well into the gas bladder. In addition, internally male members of Photolateralis exhibit lateral clearing of the silvery gas bladder lining posteriorly, corresponding in extent to the external translucent lateral stripe or windows on the flank. Including the new genus described herein, we now recognize 10 monophyletic genera of extant ponyfishes.